Bread and justice in Qajar Iran: the moral economy, the free market and the hungry poor - Cronin, S (Taylor and Francis, 2018)
In 1971, E. P. Thompson published a seminal article on eighteenth century English bread riots which was to become a foundational text for the study of such protests. Challenging older elite notions of the irrationality, illegitimacy and even criminality of the ‘mob’, Thompson situated popular direct action in times of food crises within a very specific historical, economic and, most importantly, cultural context. This context produced a deeply held adhesion among the poor to the concept of a ‘moral economy’ and an equally profound rejection of the free market as enshrined in the new political economy of the eighteenth century. This article returns to Thompson's original text in order to assess to what extent his paradigm may be useful in understanding bread riots in Iran. In particular, it examines the evidence which supports the notion that Iran experienced a ‘golden age’ of bread riots in the 1890s and early 1900s, just before and indeed contributing to the outbreak of the constitutional revolution.